Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasaan Nasabah Bank Jatim Di Surabaya - Gogi Kurniawan (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2015)
Service quality dimensions give boost to customers in Surabaya, East Java Bank to establish strong bond with the services, which in turn is expected to provide satisfaction to customers. This study aimed to analyze the influence of service quality dimensions consisting of reliability, responsiveness, and empathy towards customer satisfaction Bank of East Java, Surabaya. This study used a sample of 60 respondents customers, further testing using multiple linear regression analysis, was tested by using the F-test and t-test. The results of this study indicate that simultaneous variable reliability, responsiveness and empathy has a positive and significant impact on customer satisfaction. While partially reliability, responsiveness and empathy positive and significant impact on customer satisfaction. While variable Responsiveness dominant and significant effect. Means three dimensions of service quality has an important role in helping the needs and desires of customers to receive excellent service of the best.